HASIL PRHASIL PRODUKSI BRIKET SAMPAH ORGANIC MENGGUNAKAN METODE HYDROTHERMAL DARI CETAKAN KEDAP UDARA MELALUI TEKANAN TOURSIONALODUKSI BRIKET SAMPAH ORGANIC MENGGUNAKAN METODE HYDROTHERMAL DARI CETAKAN KEDAP UDARA MELALUI TEKANAN TOURSIONAL - Saputra, Riki; Fernanda, Yolli; Refdinal, Refdinal; Primandari, Sri Riski Putri (Departemen Teknik Mesin Fakultas Teknik Unversitas Negeri Padang, 2024)
One way to utilize organic waste waste is to process it into organic waste briquettes. Therefore, this study aims to utilize renewable energy from organic waste biomass to make briquette products that can overcome the accumulation of organic waste and obtain high-value products. Making briquettes from organic waste by applying heat and pressure is useful to get an orderly shape and a high calorific value. To obtain a solid, good and perfect briquette product, testing is carried out with temperature and moisture content regulation parameters during printing. The organic waste to be printed has become a powder that has been filtered with a sieve measuring 18 mesh. The briquettes are made using airtight molds by using threaded bolts at the time of pressing, applying heat during printing varying with temperatures of 250 ⁰C, 280 ⁰C, and 310 ⁰C, holding time of 10 minutes, and also setting the moisture content of 0%, 50%, and 80% of the dry weight of the raw material. The result of a good briquette product is obtained at a temperature of 310 ⁰C and a moisture content of 80% because it has become a solid briquette and has undergone a significant color change due to the decomposition process when the printing darkens.